2018
DOI: 10.1123/jsr.2018-0042
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of 5 Novel Reaction Time and Cognitive Load Protocols

Abstract: Context: Reaction time (RT) is crucial to athletic performance. Therefore, when returning athletes to play following injury, it is important to evaluate RT characteristics ensuring a safe return. The Dynavision D2® system may be utilized as an assessment and rehabilitation aid in the determination of RT under various levels of cognitive load. Previous research has demonstrated good reliability of simple protocols when assessed following a 24-to 48-hour test-retest window. Expanding reliable test-retest interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The Dynavision D2 system upper-extremity VMRT task has been established. 3 The Dynavision D2 includes 64 raised targets, 3 while the FitLight system upper-extremity task in this protocol included 8 lights. We concluded the upper-extremity VMRT task using the FitLight system is a reliable assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dynavision D2 system upper-extremity VMRT task has been established. 3 The Dynavision D2 includes 64 raised targets, 3 while the FitLight system upper-extremity task in this protocol included 8 lights. We concluded the upper-extremity VMRT task using the FitLight system is a reliable assessment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wilkerson et al 2 identified a relationship between upper-extremity VMRT and lower-extremity injury risk with the Dynavision D2 system (Dynavision; Dynavision International LLC, West Chester, OH). The Dynavision D2 system provides a reliable measure of VMRT, 3,4 reliant upon upper-extremity movement strategies; however, this system cannot be configured to assess lower-extremity movement strategies. 4,5 A task that can assess lower-extremity VMRT may provide greater insight into lowerextremity injury risk and potential impairments created by lowerextremity injury.…”
mentioning
confidence: 99%
“…depends on a number of distributed systems that are active in many data centers throughout the world. Efficient capacity allocation, correct setup, and tuning of various system resources are essential for the proper functioning and reliability of both the cache as well as backend servers in distributed systems, ensuring that they can handle incoming workloads [3] . Tests are an integral part of the software development life cycle.…”
Section: Introductionmentioning
confidence: 99%